Pattern of Principal Management in Implementing Student's Religious Character (Study At SMK IT Khoiru Ummah) - Deri Wanto; Siswanto Siswanto; Doti Irawati (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
The principal's management pattern in instilling religious character in students at SMK IT Khoiru Ummah is as an effort to grow the character of each student to become a noble human being. To find out the problem and get accurate data, the researcher used the method of observation, interviews and documentation. And using qualitative descriptive analysis techniques. From this research, it can be said that the principal's management pattern in instilling religious character in students at SMK IT Khoiru Ummah is a form of implementation or hard work effort to provide intakes to students about religious education through various kinds of programs that are created and arranged. The hope is that in the future students in the IT Khoiru Ummah Vocational School will become students with religious character in accordance with the Qur'an and Sunnah. The activities that are programmed and implemented are: (a) Duha prayer, (b) Reading the Qur'an and Al-Matsurat, (c) Tahsin and Tahfizh activities for students. With all these programs, it is a starting point and indicator of the success of the management pattern process carried out to instill religious character in students.